IMPACT OF PLATELETS AND PLATELET-DERIVED MICROPARTICLES ON HYPERCOAGULABILITY FOLLOWING BURN INJURY - Midura, Emily F. (Shock, 2016)
An acute burn induced coagulopathy develops after scald injury, which evolves into a subacute, hypercoagulable state. Microparticles, specifically platelet-derived MPs (PMPs), have been suggested as possible contributors. We first developed a model of burn-induced coagulopathy and then sought to investigate the role of platelets and PMPs in coagulation after burn. We hypothesized that changes in circulating platelet and PMP populations after injury would contribute to the post-burn, hypercoagulable state. A murine scald model with 28% TBSA full thickness burn injury was utilized and blood samples were collected at intervals after injury. Circulating MP populations, platelet counts, overall coagulation, and platelet function were determined. Burn injury led to hypercoagulability on post-burn day one (PBD1), which persisted 6 days after injury (PBD6). On PBD1, there was a significant decrease in platelet numbers and a decline in platelet contribution to clot formation with a concomitant increase in circulating procoagulant PMPs. On PBD6, there was a significant increase in platelet numbers and in platelet activation with no change in PMPs compared with sham. Further, on PBD1 decreased ADP-induced platelet activation was observed with a contrasting increase in ADP-induced platelet activation on PBD6. We therefore concluded that there was a temporal change in the mechanisms leading to a hypercoagulable state after scald injury, that PMPs are responsible for changes seen on PBD1, and finally that ADP-induced platelet activation was key to the augmented clotting mechanisms 6 days after burn.